Educación financiera y economía familiar en los habitantes de la parroquia Sabiango - Bustamante Torres, Kevin Patricio (2022)
Financial education is a significant factor in the economic and social development of people since it helps to understand how money works and how to manage it in the best way possible. The objective of this research is to develop a financial education and family economy program for people from Sabiango to build saving-money habits and secure their economic stability. To carry out this study, an exploratory and descriptive methodology was used, and a survey was applied as an instrument to collect data and classify people’s level of financial knowledge. The participants of this research were 55 people, each one of them representing their respective families. The findings show that the participants had a worrying lack of financial education before the training, placing them at level 2 of financial knowledge. Therefore, a guide about financial education was designed to improve the participants’ financial skills and knowledge. After the training was done, there was a percentage increase of 49.64%, placing the participants at level 4 regarding financial knowledge. They also expressed high levels of satisfaction and interest in mastering the topics, which encouraged the development of a more responsible saving and financial culture.